Mass Dimension Evaluation of the Optic Nerve Head Microvascularity in Non-Glaucomatous Optic Neuropathies - Giorgio Bianciardi; Maria Eugenia Latronico; Claudio Traversi (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2016)
In several diseases, fractal analysis has been proven useful to give contribution in diagnosis and prognosis of the patient and to improve treatments. In the present work we have evaluated the mass dimension of the vascular pattern of optic nerve head in non-glaucomatous optic neuropathic patients and healthy controls. Static fluorescein angiogram was performed and the images of the early venous phase were saved. A manual outline of the trajectories of the two-dimensional vascular network was performed down to vessels of 20 um diameter, processed to threshold the vessel network without background interference and converted into an outline of single pixels and then the fractal analysis was performed-Mass dimension evaluation of the optic nerve head microvascularity was able to differentiate health condition vs. non-glaucomatous neuropathies (p<0.01), as well optic neuritis vs. nonarteritic anterior ischemic optic neuropathy (p<0.01), with high sensitivity and specificity (p<0.0001; p<0.0001). Mass dimension index shows a significantly increased vascular complexity of the optic nerve head in cases compared with controls, also permitting to distinguish between patients affected by optic neuritis vs. nonarteritic anterior ischemic optic neuropathy. This new, fast, unexpensive, methodology may be used in helping the clinician to perform the differential diagnosis between the pathologies and to study the effect of therapies during the follow up of the patient.